Determinants of financial inclusion in North - Western Nigeria: a mediating effect of Islamic finance products adoption - Musa, Haruna (2024)
Nigeria currently ranks among the top seven countries globally with low financial inclusion. The northwest region of Nigeria mainly exhibits the highest financial exclusion rate compared to other regions, underscoring the imperative to understand the factors influencing financial inclusion in this area. This study expands upon the Theory of Planned Behavior (TPB) to examine the determinants of financial inclusion participation and the mediating effect of Islamic finance product adoption among adults in Nigeria's predominantly Muslim Northwest region. The research employs a quantitative approach within the positivist paradigm. The purposive sampling collected data from 500 adults, yielding 324 valid responses. Structural Equation Modeling (SEM) using Partial Least Squares (PLS) was utilized for data analysis. The findings reveal that all original TPB variables significantly influenced financial inclusion participation, including attitudes, subjective norms, perceived behavioral control, and behavioral intention. Additionally, government support impacted financial inclusion participation, whereas awareness and access to banking and digital channels were insignificant. Furthermore, Islamic finance product adoption significantly influences financial inclusion participation and mediates the relationships between attitudes, behavioral intentions, government support, access to banking and digital channels, and financial inclusion participation. However, Islamic finance adoption does not mediate the relationships involving subjective norms, perceived behavioral control, and awareness. The study suggests that future research should encompass other regions of Nigeria, particularly the northeast and northcentral regions, and consider integrating additional variables to explain financial inclusion. Longitudinal data replication of the model is also recommended. The study's practical implications include advocating for additional branches of non-interest banks, introducing diverse Islamic finance products, expanding agent banking in rural areas, developing digital products for youth, and enhancing financial literacy among women and the elderly to increase awareness of banking products and services